Bringing Experimental Lithic Technology to Paleoamerican Brazilian Archaeology: Replication Studies on the Rioclarense and Garivaldinense Industries - João Carlos Moreno De Sousa (EXARC Journal)
Experimental archaeology, especially experimental lithic technology, has not yet been established as a line of research in Brazil (or most of South America). This article presents the first systematic experimental research aiming the replication of Paleoamerican (or Paleoindian) lithic industries. Experimental replication of the stemmed points from Rioclarense and Garivaldinense industries were carried out in order to better understand their original technology. This article presents the results of this experiment and the comparison of the technological attributes of the replicated points and flakes to the archaeological ones. The results lead us to a discussion on some important technological aspects of the first lithic industries of Eastern South America.